Studies the effect of injection pressure with porosity level and hardness in hot chamber die Casting process / Mohd Hafiz Zainuddin, Fadhlul Wafi Keya Nordin - Zainuddin, Mohd Hafiz; Keya Nordin, Fadhlul Wafi (2005)
This project in title STUDIES THE EFFECT OF INJECTION PRESSURE WITH POROSITY LEVEL AND HARDNESS IN HOT CHAMBER DIE CASTING PROCESS concerns with porosity and hardness in hot chamber die casting. When talking about hot chamber, it is including with understanding of molten metal, plunger and analysis about the effect of injection pressure. It’s including the hardness and the hole trap (porosity). Through our experiment we have know that the injection pressure can give effect due the hardness and porosity of the product produced. When the pressure of injection is high, it can increase the hardness and decrease the porosity while when the injection pressure is less than what the ideal pressure it will give bad result to product produced.